2015
DOI: 10.1111/jdi.12423
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of glucagon‐like peptide‐1 receptor agonists and insulin for patients who developed diabetes after partial pancreatectomy

Abstract: Aims/IntroductionIt is known that after pancreatectomy, patients experience hyposecretion of endogenous insulin and frequently develop diabetes. However, it has been unclear whether combination therapy with glucagon‐like peptide‐1 receptor agonists and basal insulin is effective for such patients. In the present study, we evaluated the efficacy and safety of combination therapy with long‐acting insulin glargine and the glucagon‐like peptide‐1 receptor agonist lixisenatide in patients who developed diabetes aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The safety profile of lixisenatide was generally similar across the four background OAD groups, and consistent with the known safety profile of this class of GLP‐1 RAs. The safety data were also consistent with observations in previous international studies including Japanese patients, and Japan mono‐country studies in which lixisenatide was investigated either as monotherapy, or in combination with BI with or without an SU.…”
Section: Discussionsupporting
confidence: 88%
“…The safety profile of lixisenatide was generally similar across the four background OAD groups, and consistent with the known safety profile of this class of GLP‐1 RAs. The safety data were also consistent with observations in previous international studies including Japanese patients, and Japan mono‐country studies in which lixisenatide was investigated either as monotherapy, or in combination with BI with or without an SU.…”
Section: Discussionsupporting
confidence: 88%
“…In summary, our study showed that most short-term complications of this procedure were significantly higher than those of DP. Although DP had a higher incidence of long-term postoperative endocrine and exocrine insufficiency, this was well controlled by oral hypoglycemic agents, insulin, and pancreatic enzymes 68 , 69 . The main objective of CP is to preserve more normal pancreatic tissues to better protect the secretory function of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it is impossible to measure the quality of human pancreatic islet beta‐cells in vivo. Models involving transplantation of human pancreas into immunodeficient animals also have some limitations and effects could be influenced by many exogenous factors . Despite few studies having found any evidence of β‐cell replication in adult humans, many xenograft models have shown newly activated human pancreatic islet cells in the grafts.…”
Section: Discussionmentioning
confidence: 99%